Transformasi Budaya Adu Zatua di Nias Sumatera Utara - Maria Veronika Halawa; Aton Rustandi (Jurnal Kajian Seni, 2017)
This study describes how the cultural transformation zatua shootout that occurred in Nias. Adu zatua was originally a ritual objects Nias tribe belief that is sacred. Entering the 2000s appeared reproduction shootout zatua being secular and profane objects. Cultural traditions in Nias slowly started to change and evolve into a global culture. This study aimed to determine the cultural transformation in the shootout zatua, shape and also the value that is applied. Transformation contest zatua produce objects tourism. The strong cultural tourism makes fi ghts zatua production of a commercial characterand commodities cultural objects.